1993
DOI: 10.1152/ajpendo.1993.264.5.e763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corticosteroids in preterm sheep on adaptation and sympathoadrenal mechanisms at birth

Abstract: This study investigates the effects of prenatal corticosteroid administration on newborn sympathoadrenal mechanisms involved in postnatal adaptation. Randomly assigned preterm (122-125 days) fetal sheep were treated with hydrocortisone or saline for 60 h and delivered by cesarean section. We examined postnatal physiological adaptation, sympathoadrenal responses, cardiac beta-receptor density, and the receptor-cyclase system. We observed increased ventilatory, cardiovascular, and metabolic responses function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
2
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 4 publications
2
52
2
1
Order By: Relevance
“…Studies on animals have shown evidence of the effect of corticosteroids on the mechanisms for adaptation to extrauterine life. Stein et al 66 demonstrated, on premature lambs, that corticosteroids led to an improvement in ventilatory, circulatory and metabolic functions of the animals treated, which was related to the increase in the adenyl-cyclase activity of the myocardium. Corticosteroids are also thought to promote an increase in the expression of adrenergic receptors in vessel walls and the myocardium, which assist in cardiocirculatory stabilization at birth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on animals have shown evidence of the effect of corticosteroids on the mechanisms for adaptation to extrauterine life. Stein et al 66 demonstrated, on premature lambs, that corticosteroids led to an improvement in ventilatory, circulatory and metabolic functions of the animals treated, which was related to the increase in the adenyl-cyclase activity of the myocardium. Corticosteroids are also thought to promote an increase in the expression of adrenergic receptors in vessel walls and the myocardium, which assist in cardiocirculatory stabilization at birth.…”
Section: Resultsmentioning
confidence: 99%
“…In these circumstances, antenatal corticosteroids would also exercise a protective role in cardiorespiratory stabilization at birth 66 and their contribution towards successful adaptation to extra-uterine life would indirectly influence the frequency of respiratory distress syndrome, diminishing its occurrence. The incidence of intra-hospital death among patients who utilized antenatal corticosteroids and those who did not was also significantly lower in the treated group.…”
Section: Resultsmentioning
confidence: 99%
“…The head and neck of the fetus were delivered through a midline abdominal incision and hysterotomy as described previously (3,4,9). Fetuses received an intr amuscular injection of ketamine (10 mg/kg) and acepromazine (0.1 mglkg).…”
Section: Methodsmentioning
confidence: 99%
“…All newborn lambs were managed as described previously in delivery protocols of chronically catheterized fetuses (3,4,9). Procedures included: insertion of an umbilical artery catheter for blood sampling and blood gas monitoring; administration of 10 mL/kg heparinized placental blood within 5 min of delivery to all animals; insertion of a left ventricular catheter via the right carotid artery during continuous measurement of left ventricular pressure, left ventricular dP/dt and the injection of microspheres; administration of 5% dextrose in water into the umbilical artery and left ventricular catheters at a total rate of 4.5 mLlkg/h throughout the study protocol.…”
Section: Methodsmentioning
confidence: 99%
“…221). This therapy results in an increased ventilatory and cardiovascular response [294]. The effect is a decrease of morbidity [159], in spite of a brief period of suppression of the basal corticoid concentration.…”
Section: Therapeutic Effects Of Hormonesmentioning
confidence: 99%